1991
DOI: 10.1016/1010-7940(91)90123-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined resection of hepatoblastoma and intracaval right atrial extension with profound hypothermia and circulatory arrest

Abstract: Hepatoblastoma is an uncommon liver neoplasm in children but its intraatrial extension through the inferior vena cava is extremely rare. The case described is a 3-year-old boy in whom profound hypothermia and circulatory arrest were used to resect a hepatoblastoma and its extension to the right atrium. This technique allows maximal resection and relief of venous obstruction from atrial extension of hepatoblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
0
8
0
2
Order By: Relevance
“…Later, further reports of major HBL resections using the CPB have been reported, as summarized in Table 1. Many cases have been associated with major complications such as post-operative dead for pulmonary embolism (possibly related to tumoral thrombi spreading during liver mobilization) [9]; ischemic cholangiopathy requiring subsequent LT [10]; residual tumoral thrombi in major vessels [6].…”
Section: Discussionmentioning
confidence: 99%
“…Later, further reports of major HBL resections using the CPB have been reported, as summarized in Table 1. Many cases have been associated with major complications such as post-operative dead for pulmonary embolism (possibly related to tumoral thrombi spreading during liver mobilization) [9]; ischemic cholangiopathy requiring subsequent LT [10]; residual tumoral thrombi in major vessels [6].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier strategies have described CPB with circulatory arrest to resect hepatoblastomas with intracardiac extension. 4,5 In our case, the hepatectomy was performed prior to systemic heparinization, to enable hemostasis of the liver bed before institution of CPB. We avoided circulatory arrest which has the potential to cause neurological deficits.…”
Section: Discussionmentioning
confidence: 97%
“…Hepatic resection was performed under cardiopulmonary bypass with hypothermic perfusion. Previously, some cases were associated with postoperative mortality or morbidity, such as postoperative death due to pulmonary embolism, 23 and ischemic cholangiopathy requiring subsequent LT 25 . However, recent studies reported that the postoperative course was uneventful and that patients were discharged within a month after the operation 6,9,12,26 .…”
Section: Discussionmentioning
confidence: 99%